In Vitro and In Vivo Effects of Nonsteroidal Anti-inflammatory Drugs and Aspirin on Rabbit Esophageal Epithelium - Kıpçak, Sezgi; Çağanoğlu, Doğa; Ergün, Pelin; Bor, Serhat (Turkish Journal of Gastroenterology, 2022)
Background: Gastroesophageal reflux disease has a high incidence of 23%, with 29% of those with gastroesophageal reflux disease consuming nonsteroidal anti-inflammatory drugs. There are insufficient data concerning the effects of nonsteroidal anti-inflammatory drugs on the esophageal tissue. We aimed to examine the effects of well-known nonsteroidal anti-inflammatory drugs using electrophysiologic criteria on the rabbit esophageal epithelium. Methods: Esophageal epithelium mounted on Ussing chambers enabled in vitro investigation of the electrophysiological properties. Doses of 1 mg/mL, 2.5 mg/mL, 5 mg/mL ibuprofen, naproxen, and aspirin were dissolved in dimethyl sulfoxide and added to the luminal side. Esophagi were cannulated from both sides for the administration of high-dose ibuprofen in vivo, and the potential difference was monitored. Results: Ibuprofen and aspirin inhibited tissue transport functions in a dose-dependent manner. pH 4 acid and 0.1 mg/mL ibuprofen alone were not harmful; however, the combination of these agents had an additive and significance effect: 78% decrease in the potential difference and 85% decrease in the short-circuited current (Isc). The change in the potential difference in the in vivo experiments (5 mg/mL ibuprofen) was similar (52 ± 7% decrease) with in vitro experiments in the first 30 minutes. Conclusion: Nonsteroidal anti-inflammatory drugs were harmful to the rabbit esophageal epithelium in both the in vitro and in vivo experiments. Even though aspirin and ibuprofen affected the transport mechanisms of the esophageal epithelium, the dose-dependent decrease of tissue potential difference and Isc with ibuprofen was more pronounced than those with aspirin. The combination of harmless doses of ibuprofen and acid demonstrated that even low acidic conditions can create a disruptive environment.